From Ruskin’s stones to Velarde’s adobes: Research and Development (R&D) in the preservation of Peruvian built heritage. The Bruno Roselli Chair as a model of public, private and academic partnership - Abarca Torres, Héctor (2018)
The current concepts on management of the built Heritage led by ICOMOS and the European Council are moving forward beyond the building capacity of our current system of heritage management. However there are a lot of complex projects that are being carried out in partnerships between Peruvian academic institutions and major international conservation organizations. This paper lists some of the local and foreign experiences that can help to create a shift that will allow conservation as Research and Development (R&D) 2 ventures to connect public, private and academic partners through the Bruno Roselli Chair, a research program that will streamline and support a contemporary approach of the Peruvian built heritage.